2018
DOI: 10.1088/1361-648x/aacd76
|View full text |Cite
|
Sign up to set email alerts
|

Photo-excited dynamics in the excitonic insulator Ta2NiSe5

Abstract: The excitonic insulator is an intriguing correlated electron phase formed of condensed excitons. A promising candidate is the small band gap semiconductor TaNiSe. Here we investigate the quasiparticle and coherent phonon dynamics in TaNiSe in a time resolved pump probe experiment. Using the models originally developed by Kabanov et al for superconductors (Kabanov et al 1999 Phys. Rev. B 59 1497), we show that the material's intrinsic gap can be described as almost temperature independent for temperatures up to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Such a situation cannot be treated in our simple mean-field approximation. Nevertheless, we may point out that our calculations could yield some experimental aspects such as the enhancement of the excitonic order [20,21], coherent order parameter oscillations [22,23], as well as the insulator-to-metal transitions reported recently [48]. The improved method of calculations beyond the mean-field approximation based on more realistic models will be required for future quantitative studies of the nonequilibrium dynamics of the excitonic insulator states.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such a situation cannot be treated in our simple mean-field approximation. Nevertheless, we may point out that our calculations could yield some experimental aspects such as the enhancement of the excitonic order [20,21], coherent order parameter oscillations [22,23], as well as the insulator-to-metal transitions reported recently [48]. The improved method of calculations beyond the mean-field approximation based on more realistic models will be required for future quantitative studies of the nonequilibrium dynamics of the excitonic insulator states.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Finally, let us discuss possible experimental significance of our results, taking a quasi-1D direct-gap semiconductor Ta 2 NiSe 5 as an example. The energy of the laser light so far used in experiment is 1.55 eV [20][21][22][23], which is very large in comparison with the observed band gap 160 meV [10,45,46]. Thus, our two-band model seems to be too simple to take into account the excitations in such a high-energy scale where other orbitals such as Se 4p become relevant.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In parallel, studies based on density functional theory (DFT) calculations disagree on its capability to capture the normal state of Ta 2 NiSe 5 , notably due to the difficulty of finding an appropriate functional for describing this material [11,12,17,18]. In addition, time-resolved studies based on pump-probe techniques support the existence of an excitonic insulator ground state at low temperature [14,[19][20][21][22]. It has been notably shown that this correlated ground state makes it possible to control the size of the band gap in Ta 2 NiSe 5 , depending on the excitation density [14].…”
Section: Introductionmentioning
confidence: 99%
“…4 For the present study, we have performed the measurements of time-and angleresolved photoemission spectroscopy (TARPES) to obtain such evidence that Ta2NiSe5 is actually an excitonic insulator from its pump-fluence dependence of the photoexcitation dynamics. Whereas several time-resolved studies on Ta2NiSe5 have been reported so far [14][15][16][17] , the present study is quite unique in that we employ a pump laser with shorter pulse duration (~ 30 fs), and extreme ultra violet (XUV) laser from high harmonic generation for probe pulses. Whereas we have employed 1 kHz for the repetition rate of the laser in order to generate higher order harmonics, this makes higher pump fluence available compared to higher repetition rate with the same average power of pump pulses.…”
mentioning
confidence: 99%